The pitfalls of “virtual tourism”: Challenges for small peripheral communities - Sampaio, S. (Colóquio Internacional “Moving Pictures: Tourism, Cinema and Peripheral Spaces”, 2018)
My paper discusses the concept of “virtual tourism” in the context of cinema-tourism studies. One of the problems with this concept is that it tends to take for granted and reinforce dematerialised approaches to cinema and tourism. I suggest that bringing the materiality of film and tourism back to cinema-tourism studies may help small peripheral communities become aware of what is at stake in many film-tourism projects and models. Rather than taking a pre-assigned place in the general scheme of the ‘global sign industries’ (Tzanelli 2007), small peripheral communities should feel encouraged to develop articulated filmmaking and hospitality practices that take into account key aspects like: how they wish to be represented; what role they wish to play in the process; how they expect to deal with the project’s outputs and impacts. I argue that key identity issues should merit extended public discussion and a widely participated plan of action.